Public-Private Sector Wage Differentials and Returns to Education in Djibouti - Anós Casero, Paloma (World Bank, Washington, DC, 2012)
Do public sector workers earn a wage premium in Djibouti and are the returns to education different across the sectors? The authors estimate private and public sector wage earnings using 1996 household survey data, while controlling for selectivity using Heckman's two stage approach. They find that Djiboutian public sector employees earn a wage premium, independent of their personal attributes and human capital endowments, and are more likely to be males and have parents in the public sector. Workers in the public sector earn higher private rates of return to education than do private sector workers with post-secondary schooling. These results raise concerns about current government hiring and wage-setting practices that generate distortions in the labor market and are not efficiently allocating labor and public resources.